The western Christian presence in the Russias and Qajar Persia, c.1760-1870 - Flynn, Thomas S. (Studies in Christian Mission, 2016)
Winner of The 2018 Saidi-Sirjani Book Award In The Western Christian Presence in the Russias and Qājār Persia, c.1760-c.1870 , Thomas O'Flynn vividly paints the life and times of missionary enterprises in early nineteenth-century Russia and Persia at a moment of immense change when Tsarist Russia embarked on an expansionist campaign reaching to the Caucasus. Simultaneously he charts the relationship between the new Persian dynasty of the Qājārs and missionary activity on the part of European and American missionaries. This book reconstructs that world from a predominantly religious perspective. It recounts the sustaining ideals as well as the everyday struggles of the western missionaries, Protestant (Scottish, Basel and American Congregationalist) and Catholic (Jesuit and Vincentian). It looks at the reactions of diverse tribal peoples, the Tatars of the North Caucasus, the Kabardians and Circassians. Persia was the ultimate goal of these missionaries, which they eventually reached in the 1820s. Altogether this study throws light on the troubled course of history in West Asia and provides the background to politico-religious conflicts in Chechnya and Persia that persist to the present day.